Inclusive Growth, Energy Poverty and Digital and Social Development: Cross-Country Analysis of the European Union - Blanka Tundys; Agnieszka Bretyn (Energies)
The present study delves into a critical concern on the relationship between energy poverty, digital and social development and inclusive growth. The main research hypothesis assumes a positive relationship between these areas, although differences between countries are inevitable. Therefore, the following research questions were asked: Is the impact of the level of energy poverty on inclusive growth the same in different EU countries? How does the use of renewable energy sources in individual countries affect energy poverty and thus inclusive growth? What is the link between energy poverty, digital and social development and inclusive growth in the countries studied. This study uses a critical analysis of the literature and methods of descriptive and mathematical–statistical tools/model. The main conclusions and findings of the analysis reveal that the link between energy poverty, use of renewable energy resources, digital and social development and inclusive growth varies across EU countries. The results of our analyses may be useful, for example, for government decision makers in terms of actions aimed at eliminating energy poverty through the country’s use of sustainable energy sources as well as designing and implementing actions aimed at increasing digital and social development, which will then contribute to inclusive growth.